Menggali Nilai-nilai Pendidikan dalam Sajak-sajak Angga Wijaya: dari Kesadaran Diri hingga Pencarian Spiritual - Ananda, Refisa; Badriyah, Ratu; Yunianika, Ika Tri (Indonesian literature Program, Faculty of Humanities, Diponegoro University, 2024)
So far, there has been limited research on the exploration of educational values in poetry. This study aims to explore how poetry reflects moral and spiritual values, as well as how it can be used as an effective educational tool. The research employs a qualitative analysis method, focusing on hermeneutics. The primary data source for this study is a collection of poems by Angga Wijaya. The findings reveal that Angga Wijaya's poems invite readers to reflect on life and discover deeper meaning through self-awareness. His works emphasize the importance of letting go of the past, embracing change, and practicing patience in facing life's challenges. The recurring use of moon imagery guides readers on a spiritual journey, while themes of love and respect highlight the values of unity and compassion. The study suggests that Angga Wijaya's poetry can serve as an effective medium for teaching character education.